The complete mitochondrial genome of a stonefly species, Suwallia bimaculata (Plecoptera: Chloroperlidae). Issue 2 (3rd July 2019) - Cao, Jinjun; Wang, Ying; Chen, Mengdan; Yuan, Mingyang; Li, Weihai
Abstract: The stonefly Suwallia bimaculata belongs to the Chloroperlidae. The mitogenome of S. bimaculata was sequenced and annotated, the new representative of the complete mitogenome of the genus Suwallia . The entire genome of S. bimaculata is 16, 125 bp totally with an A + T content of 68.5%, consisting of 13 protein-coding genes, two ribosomal RNAs, 22 transfer RNAs, and a 1, 210 bp control region. All genes have the similar locations and strands with that of other published species of Plecoptera. Most PCGs use typical start/stop codon, whereas ND5 use GTG as start codon. And, COII and ND5 stopped with incomplete terminaton signal T. Phylogenetic analysis was performed using the Bayesian (BI) method and Maximum-likelihood (ML) methods based on 13 protein-coding genes and two ribosomal RNAs showed that S. bimaculata was the sister group to Suwallia teleckojensis and the clade Suwallia was closely to four perlodid species. More chloroperlid data was needed for further study of phylogeny in Chloroperlidae.